Prospective study on embolization of intracranial aneurysms with the pipeline device: the PREMIER study 1 year results. (15th July 2019) - Hanel, Ricardo A; Kallmes, David F; Lopes, Demetrius Klee; Nelson, Peter Kim; Siddiqui, Adnan; Jabbour, Pascal; Pereira, Vitor M; Szikora István, Istvan; Zaidat, Osama O; Bettegowda, Chetan; Colby, Geoffrey P; Mokin, Maxim; et al.
Abstract : Background: Preliminary clinical studies on the safety and efficacy of the pipeline embolization device (PED) for the treatment of small/medium aneurysms have demonstrated high occlusion rates with low complications. Objective: To evaluate the safety and effectiveness of the PED for treatment of wide necked small and medium intracranial aneurysms. Methods: PREMIER is a prospective, multicenter, single arm trial. Patients were treated with the PED for unruptured wide necked aneurysms, measuring ≤12 mm along the internal carotid artery or vertebral artery, between July 2014 and November 2015. At 1 year post-procedure, the primary effectiveness endpoint was complete occlusion (Raymond grade 1) without major parent vessel stenosis (≤50%) or retreatment, and the primary safety endpoint was major stroke in the territory supplied by the treated artery or neurologic death. Results: A total of 141 patients were treated with PEDs (mean age 54.6±11.3 years, 87.9% (124/141) women). Mean aneurysm size was 5.0±1.92 mm, and 84.4% (119/141) measured <7 mm. PED placement was successful in 99.3% (140/141) of patients. Mean number of PEDs implanted per patient was 1.1±0.26; a single PED was used in 92.9% (131/141) of patients. At 1 year, 97.9% (138/141) of patients underwent follow-up angiography with 76.8% (106/138) of patients having met the study's primary effectiveness endpoint. The combined major morbidity and mortality rate was 2.1% (3/140). Conclusions: Treatment of wide necked small/medium aneurysms with the PED results in high rates of complete occlusion without significant parent vessel stenosis and low rates of permanent neurologic complications. Trial registration: NCT02186561 .